Controlled motivation and physics achievement: a serial mediation analysis through self-efficacy and learning strategies in Chinese high school students - Li, Xiao; Lin, Xue; Lin, Jingxian; Yan, Mengting (Frontiers in Psychology, 2026)
BackgroundIn high-stakes examination contexts such as China’s Gaokao system, students frequently experience controlled motivation characterized by external pressure and learning anxiety. While research consistently demonstrates that controlled motivation undermines academic achievement, the psychological mechanisms through which this occurs remain underspecified. This study examined whether and how controlled motivation influences physics achievement through sequential effects on self-efficacy beliefs and learning strategy use among Chinese high school students.MethodsA total of 496 s-year high school students (65.9% male; M age = 16.98 years) from three schools in Zhejiang Province completed validated measures of controlled motivation, physics self-efficacy, learning strategies, and physics achievement. Serial mediation analysis using Hayes’ PROCESS Model 6 tested the hypothesized pathways through which controlled motivation influences achievement.ResultsThe negative association between controlled motivation and physics achievement operates primarily through psychological and behavioral mechanisms rather than through direct pathways. These findings suggest that interventions targeting self-efficacy enhancement and learning strategy support may effectively buffer against the detrimental effects of external pressure in high-stakes educational contexts. This research integrates self-determination theory, social cognitive theory, and self-regulated learning theory into a unified framework for understanding motivation-achievement relationships.ConclusionThese findings suggest that interventions targeting self-efficacy enhancement and learning strategy instruction could potentially buffer against the detrimental correlates of external pressure in high-stakes educational contexts. The research contributes to theoretical understanding by demonstrating empirical support for an integrated framework combining self-determination theory, social cognitive theory, and self-regulated learning theory in explaining motivation-achievement relationships.